A CASE STUDY OF KAIZEN IMPLEMENTATION IN SMI - A. P., Puvanasvaran; S.T. Kerk, Robert; A. R., Ismail (2010)
Kaizen is a concept that focuses on improving a work area or an organization in incremental steps. Many organizations have begun to incorporate the philosophy of kaizen through the use of kaizen methodology. The first well-known and most frequently cited proponent of kaizen was Imai, who wrote KAIZEN – The Key to Japan’s Competitive Success (1986). He outlined the concept, its core values and principles, its relation to other concepts and the practices used in the improvement process. This paper illustrates about kaizen case study in Small Medium Industries (SMI) Company that is ABC Company, which produce machines spare part and food processing machines. This case study is focused on reducing lead time of sales order processing. Kaizen steps are used as guidelines and PDCA Cycle is choosing as problem solving approach to conduct the case study. The properly tools and techniques such as 5why, Work Instruction Sheet, Pareto diagram, Process Mapping, PDCA Cycle and brainstorming were used. The kaizen implementation has reduced the percentage of time losses which is 48.44%. More than that, sales order processing lead time was reduced about 6.98% and production lead time reduced about 14.93%. These results have proved the effectiveness of kaizen methodology.